A review of residential blockchain internet of things energy systems: resources, storage and challenges - Mohd Aman, Azana Hafizah; Shaari, Nor Azuwan; Attarbashi, Zainab; Iftikhar, Saman; Bawazeer, Shaikhan; Osman, Siti Hasanah; Hasan, Nor Shahida (Elsevier, 2024)
The Internet of Things (IoT) and Blockchain paradigms have offered significant benefits in recent technological innovations. Blockchain has been rated one of the top ten strategic technologies in a recent Gartner survey, and it is increasingly being employed in a range of industries. Blockchains provide transparent, tamper-proof, and secure platforms that, enables ground-breaking commercial solutions. Nonetheless, the use of blockchain technology for IoT Smart Residential energy systems looks to be relatively unexplored. In fact, most IoT devices are powered by a battery with a short life span. Generating and managing energy on an infinite scale is a much more ambitious goal than relying solely on battery power. Hence, this topic is addressed in this article, focusing on the IoT energy systems, renewable energy resources, and how energy is successfully stored. By thoroughly evaluating the literature and existing research cases, this article contributes to the state-of-the-art. Our study examines the opportunities, challenges, and constraints for the evolving peer-to-peer energy systems and blockchain-IoT applications. The study concludes with the hurdles that technology must overcome in order to move beyond the hype phase and into mainstream acceptance.